The threat of religious extremism in Kazakhstan and the role of religious education in limitation (Eurasian Journal of Religious Studies, 2021)
In the context of the current spiritual revival in the country, it is important to reconsider the issue of religion, which is the basis of this spirituality, in order to distinguish the correct understanding of religion from false religion, to identify the causes and consequences of negative phenomena such as radicalism, extremism and terrorism. The article is dedicated to the threat of religious extremism in Kazakhstan, its manifestations and factors, as well as the role of religious education in its restriction. The aim of article is to discuss the current religious, cultural situation and the struggle with religious extremism in the country. Extremism is a very complex phenomenon that always manifests itself. The purpose of the article is to analyze the emergence of extremism in Kazakhstan, to identify conflicts of interest of people underlying this phenomenon and historical, socio-economic, religious differences. The causes of extremism differ in each society and depend on the objective and subjective situation in that society. However, there is a basic situation of the emergence and spread of extremism. The main factors of the emergence of extremism at the present stage, experts in the world propose: a sharp decrease in the standard of living of most of the local population; distortion of public administration and political institutions. Key words: religious consciousness, extremism, terrorism, islamophobia, religious education
Keywords: religious consciousness; extremism; terrorism; Islamophobia; religious education